Parental burnout of parents of primary school students: an analysis from the perspective of job demands-resources - Zhao, Jiangtao; Hu, Hua; Zhao, Siqin; Li, Wenwen; Lipowska, Małgorzata (Frontiers in Psychiatry, 2023)
Objective: Based on the theory of Job Demands-Resources （JD-R）, this study explored the relationship among parenting requirements, parenting resources and parental burnout of primary school students’ parents, and examined the mediating role of psychological resilience on parenting resources. Methods: 600 valid parents of students from 3 Chinese primary school participated an online survey. The Parenting Stress Scale, Perceived Family Support Scale, Psychological Resilience Scale and Parental Burnout Scale were used in the survey. The level of parental burnout were analysed. Results: Parenting stress was positively correlated with parental burnout, perceived family support, resilience and parental burnout were negatively correlated, psychological resilience played a partial mediating role between perceived family support and parental burnout, both family support and psychological resilience played a moderating role between parenting stress and parental burnout. Conclusion: The JD-R theory is applicable to child rearing. Parental burnout can be reduced by increasing family support and improving resilience. In the same way, the impact of parenting stress on parental burnout can be buffered under high-pressure situations.